1998
DOI: 10.1007/s11626-998-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Application and evaluation of the alamarblue assay for cell growth and survival of fibroblasts

Abstract: Cell proliferation assays are essential to developing an understanding of the molecular mechanisms that modulate cell growth and differentiation. In this paper, we describe the application of alamarBlue, a new and versatile metabolic dye, for the detection of Swiss 3T3 fibroblast proliferation and/or survival. As a redox indicator, alamarBlue is reduced by reactions innate to cellular metabolism and, therefore, provides an indirect measure of viable cell number. Various assay parameters were optimized for a 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 23 publications
3
101
0
Order By: Relevance
“…The commercialized Alamar blue dye contains 0.1 mg/ml of resazurin. The manufacturer's report and most other studies suggested the use of one-tenth dilution of Alamar blue so, for our study, we opted for a final concentration of 0.01 mg/ml of resazurin (5,11,16,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The commercialized Alamar blue dye contains 0.1 mg/ml of resazurin. The manufacturer's report and most other studies suggested the use of one-tenth dilution of Alamar blue so, for our study, we opted for a final concentration of 0.01 mg/ml of resazurin (5,11,16,32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been commercialized since 1993 as Alamar blue dye (10) as a viability cell test and has been assessed several times on different types of cells for its cytotoxicity reliability, i.e. fibroblasts (11), immortalized and cancer cell lines (5,12), tumor necrosis factor-hypersensitive cells (13), and for its cell proliferation reliability on mouse and human lymphocytes (6,14) and primary neuronal cell culture (15). Viability measurement using resazurin is similar to or greater than traditional tetrazolium salts (MTT, XTT) and [ 3 H] thymidine assay techniques (5,10,11,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The droplets' chemical isolation was used to implement a single-cell performancebased assay. For this, we chose to investigate the metabolic activity of fibroblasts (NHDF) using the alamarBlue assay, which is used routinely to estimate the number of metabolically active cells in bulk (47). In the presence of a live cell, its fluorescence turnover linearly increases over time.…”
Section: E)mentioning
confidence: 99%
“…Cells were treated with 10 nmol/L Δ4A or 1 nmol/L E 2 and various concentrations of test compounds (0.2, 1, 3, 10, and 50 μmol/L) for 3 d or 6 d. Each concentration was tested in triplicate. The proliferation assay was performed using the alamarBlue® assay as previously described [33,34] . A Safire 2 microplate reader (Tecan, Switzerland) was used to detect the fluorescent intensity at Ex 560 nm/Em 590 nm.…”
mentioning
confidence: 99%